Association Between Early-Life Nutritional Practices and Children's Feeding and Swallowing Skills - Putri, Anggi Resina; Mangunsong, Roy Romey Daulas (Indonesian Journal of Medicine, 2026)
Background: Children's feeding and swallowing abilities are vital functions that support optimal growth and development, involving the complex coordination of muscles and neural systems to ensure the safe and efficient consumption of food. This study aimed to analyze the role of early-life nutritional practices in the development of feeding and swallowing abilities among children in the Surakarta region using logistic regression analysis. Subjects and Method: This cross-sectional study was conducted in Surakarta, Central Java, from April to August 2025 and involved 50 children selected through purposive sampling. The independent variables were lactation-based early nutrition and post-lactation complementary nutrition practices, while feeding and swallowing abilities served as the dependent variables. Data were collected through interviews, observations, questionnaires, and the Dysphagia Disorder Survey (DDS). Associations between variables were analyzed using logistic regression in Stata 13. Results: The results of this study indicated that both a history of appropriate lactation-based early nutrition and appropriate post-lactation complementary nutrition practices were significantly associated with children's feeding and swallowing abilities. Children with a history of lactation-based early nutrition (b= 3.13; 95% CI= 0.97 to 4.27; p= 0.002) and appropriate post-lactation complementary nutrition practices (b = 2.48; 95% CI = 0.49 to 4.23; p = 0.013) were more likely to demonstrate appropriate feeding abilities. Similarly, children with a history of lactation-based early nutrition (b = 3.11; 95% CI= 1.08 to 4.76; p= 0.002) and appropriate post-lactation complementary nutrition practices (b= 3.03; 95% CI= 1.10 to 5.18; p= 0.002) were more likely to exhibit appropriate swallowing abilities. Conclusion: This study concludes that both lactation-based early nutrition and appropriate post-lactation complementary nutrition practices are significant determinants of feeding and swallowing abilities in children.